Notes about the Introduction of Christianity in Gallaecia trough the Analysis of Ceramics with Christian Symbols - Fernández Fernández, Adolfo (Gerión. Revista de Historia Antigua, 2021)
From the 4th century Christianism, already the official religion of the Empire, spreads through different ways, including the incorporation of its symbolism in all types of mobile supports. A phenomenon that will increase along the time, especially during the 6th century. One of the most common supports will be pottery, garnished with different types of Christian symbols, used from the middle of the 4th century, that will gradually replace the pagan symbols from the previous centuries. Gallaecia, especially its cities and harbours, will be influenced by the new traditions, arrived from foreign lands like the North of Africa and Eastern Mediterranean, thanks to its privileged location in the Atlantic commercial routes. This paper will analyse the pottery evidence with Christian symbolism and their archaeological contexts, to show the importance of the penetration and evolution of Christianism and its symbolism in Gallaecia from the 4th to the 7th century.